The Politics of Indonesia's Energy Transition: Balancing Coal Dependency and Net-Zero Commitments - Raka Aditya Wibisana (Indonesian Political Transformation, 2025)
Indonesia's commitment to achieving net-zero emissions while maintaining economic growth presents one of the most significant political and governance challenges in Southeast Asia. Although international attention has focused on Indonesia's renewable energy potential and participation in global climate initiatives, domestic political dynamics shaping the energy transition remain insufficiently understood. This study investigates how competing political, economic, and institutional interests influence Indonesia's transition from coal dependency toward a more sustainable energy system. Adopting a political economy perspective, the research integrates policy analysis, stakeholder mapping, energy sector data, and interviews with government officials, energy companies, environmental organizations, and international development partners. The analysis reveals that Indonesia's energy transition is characterized by complex negotiations among state institutions, fossil fuel industries, local governments, and international climate finance mechanisms. While substantial policy progress has been achieved through renewable energy commitments and international partnerships, implementation continues to face institutional fragmentation, investment uncertainty, and conflicting development priorities. The article argues that successful energy transition depends not only on technological innovation but also on governance reforms capable of aligning political incentives, regulatory consistency, and social equity considerations. By examining Indonesia as a representative emerging economy, this study contributes to global debates concerning just energy transition, climate governance, and sustainable development. The findings provide policy insights relevant for developing countries attempting to reconcile economic development objectives with international climate commitments and long-term environmental sustainability.